Warming alters juvenile carp effects on macrophytes resulting in a shift to turbid conditions in freshwater mesocosms. Issue 1 (26th October 2021) - Zhang, Peiyu; Zhang, Huan; Wang, Huan; Hilt, Sabine; Li, Chao; Yu, Chen; Zhang, Min; Xu, Jun
Abstract: Multiple stressors such as climate change and eutrophication are responsible for the global decline in macrophytes in lakes. The loss of this key component can result in turbid conditions and a loss of important ecosystem functions and services, particularly in shallow lakes. Benthivorous fish, which can increase in abundance during eutrophication, can adversely affect macrophytes through physical disturbance, cascading effects on turbidity, suspended and attached algae (phytoplankton and periphyton) and direct consumption. However, whether warming amplifies their effects on macrophytes and can trigger regime shifts remains unexplored. Here, we tested the single and combined effects of warmer water (+4.5°C) and the widespread benthivorous juvenile common carp Cyprinus carpio on two different types of aquatic macrophytes in 24 mesocosms (2, 500 L each). We monitored phytoplankton, periphyton, turbidity and the abundance of the submerged curly leafed pondweed Potamogeton crispus and the floating‐leaved water chestnut Trapa bispinosa during their growing season. These species dominated successively in spring and summer. Warming alone advanced the growing season of P. crispus by 17 days. Juvenile carp decreased the abundance of the more palatable P. crispus, but promoted the abundance of T. bispinosa, supporting an ecosystem shift to a dominance of floating‐leaved macrophytes. Fish also substantially increased water turbidity and the biomass of phytoplankton and periphyton. Warming amplified juvenile carp effects on turbidity and submerged macrophytes, but also decreased the abundance of floating‐leaved macrophytes leading to an overall macrophyte decline and increase in water turbidity. Synthesis and applications . Our study provides the first experimental evidence for a warming‐induced regime shift from clear‐water conditions dominated by submerged or floating/floating‐leaved macrophytes to a turbid state in shallow aquatic ecosystems. The regime shift was triggered by the impacts of warming on benthivorous fish (juvenile common carp) rather than on macrophytes. Lowering nutrient loading and other measures to reduce the abundance of benthivorous fish (e.g. fish removal and piscivorous fish restocking) thus may become increasingly important for the management of shallow lakes under global climate change. Abstract : Our study provides the first experimental evidence for a warming‐induced regime shift from clear‐water conditions dominated by submerged or floating/floating‐leaved macrophytes to a turbid state in shallow aquatic ecosystems. The regime shift was triggered by the impacts of warming on benthivorous fish (juvenile common carp) rather than on macrophytes. Lowering nutrient loading and other measures to reduce the abundance of benthivorous fish (e.g. fish removal and piscivorous fish restocking) thus may become increasingly important for the management of shallow lakes under global climate change. 中文摘要: 气候变化和富营养化等多重胁迫是湖泊水生植物衰退的重要驱动因子。水生植物衰退会导致湖泊由清水态向浊水态转变, 进而削减生态系统功能和服务。底栖鱼类可以通过扰动和营养级联效应增加水体浊度, 促进藻类 (浮游植物和附着藻) 的生长, 或者直接牧食水生植物, 从而抑制水生植物生长。底栖鱼类丰度通常随着富营养化的加剧而增加。但气候变暖是否会加剧底栖鱼类对水生植物的影响, 进而导致稳态转换的研究仍比较匮乏。 本研究通过二十四个中宇宙系统模拟气候变暖 (水温+4.5°C) 和有无底栖鱼类, 探讨二者是如何单独及共同影响不同生活型水生植物 (早春沉水植物菹草和夏季浮叶植物菱) 。实验过程中同步监测了的浮游植物、附着藻、水体浊度以及水生植物的丰度变化。 实验结果表明气候变暖提前了菹草的生活周期 (17天) 。鲤鱼抑制了菹草的生长, 但是促进了菱的生长, 增加了水体浊度并促进了浮游植物和附着藻的生长, 导致生态系统转变为了以浮叶植物为主的稳态系统。气候变暖加剧了鲤鱼对沉水植物的影响, 而且抑制了浮叶植物的生长, 导致水体浊度进一步升高。 本研究显示气候变暖可能导致浅水湖泊生态系统由以水生植物为主的清水态转变为浊水态, 并不是由于变暖直接影响水生植物, 而是通过底栖鱼类间接产生。随着气候变化的加剧, 未来的湖泊管理, 除了要继续削减营养盐输入, 还应当通过生物调控 (削减底栖鱼类和增加肉食性鱼类) 控制底栖鱼类的数量。